Pengujian Black Box Pada Aplikasi Pembelajaran Bahasa Mandarin Berbasis Android - Saman, Putri; Indah Ratnasari, Chanifah (Jurnal Teknik Informatika UMUS, 2022)
Mobile devices are widely regarded as the most widely used information and communication technologies. There are numerous advantages to using mobile technology for language learning. This study put the Android-based Mandarin language learning application to the test. A black box test method was used. This app is designed to help users learn Chinese by reading. This application's main module is Reading, which has two sub-modules: Book & Articles and Word List & Comprehension Score. Based on the test results, one test case must be followed up on in order for the system to be more efficient and perform as expected.